An investigation on the role of L2 proficiency in adult learners' L2 morphological performance. (18th March 2021) - Li, Ying
Abstract: This study investigated whether adult learners could eventually achieve nativelike proficiency in L2 inflectional morphology that is not instantiated in their L1 with the increase of L2 proficiency. The participants were 47 L1‐Chinese of L2‐English speakers. They were divided into three groups according to their levels of English proficiency, and their morphological performance in L2‐English plurals was individually tested with a self‐paced word‐by‐word reading task and an oral interview. According to the results: (1) all the three groups showed a reliable degree of sensitivity to English plurals; although L2 proficiency was non‐significant in their overall performance, the advanced participants displayed a more similar pattern of performance to the native English speakers as compared to the less‐advanced ones; and (2) the participants' production accuracy increased with the increase in English proficiency. Overall, the findings suggested that adult L2 learners could eventually acquire L2 morphology with the increase of L2 proficiency. 摘要: 这篇论文研究了成年二语学习者能否随着第二语言水平的提高而最终在二语屈折形态的习得上达到母语水平, 尤其是对于那些在他们母语中缺失的二语形态特征。 实验参与者是47位母语为中文、第二语言为英文的成年人。根据他们的英文水平, 这47位参与者被分成了三组。他们的二语屈折形态)英文规则复数名词(水平通过自定义速度的逐字阅读任务和口头访谈被测试了。根据参与者在测试中的表现发现:1. 在逐字阅读任务中, 三组参与者对英文规则复数名词都表现出了显著的敏感性;尽管他们的英文水平对他们的整体表现没有显著影响, 但跟英文水平较低的参与者相比, 英文水平较高的参与者在该任务中的表现与英文母语者更为相似; 2. 在口语访谈中, 参与者口语中的英文规则复数名词的准确性与他们的英文水平成正比。总体而言, 这项研究表明, 在第二语言屈折形态的习得中, 成年二语习得者会随着第二语言水平的提高而最终获得母语水平。